2019
DOI: 10.2478/ebtj-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Future Biotechnology

Abstract: The field of biotechnology is large and could be considered tritely as simply the development of technology that is based on biology. It is clear that the concepts of biotechnology can spread to cover many different fields of application and so the future developments in biotechnology will be similarly wide-ranging across many fields of applications. Here we focus onto medical biotechnology and further refine our discussion onto considering aspects of genetics and nanotechnologies that could impact on the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Artificial cell research has seen the development of artificial intelligence (AI) as a growing field (71). Incorporating AI and machine learning algorithms into artificial cells has greatly improved their real-time monitoring skills, adaptive reactions and predictive modeling (72).…”
Section: The Future Of Artificial Cell Technologymentioning
confidence: 99%
“…Artificial cell research has seen the development of artificial intelligence (AI) as a growing field (71). Incorporating AI and machine learning algorithms into artificial cells has greatly improved their real-time monitoring skills, adaptive reactions and predictive modeling (72).…”
Section: The Future Of Artificial Cell Technologymentioning
confidence: 99%
“…The World Health Organization (WHO) has documented three million instances of agricultural-chemical-related harm in nonindustrialized countries (29). Prolonged and indiscriminate use of agrochemicals adversely affects soil biodiversity, agricultural sustainability, and sanitation (30).Studies have reported adverse impacts on biodiversity and carbon sequestration associated with the projected expansion of croplands in the future (31).…”
Section: Effect Of Microorganisms On Ecosystems Effect Of Microorgani...mentioning
confidence: 99%
“…Because the cornea is an avascular structure, bioprint- Bioprinting may also be employed to prepare drugs and drug delivery systems (55). Predicting the efficacy and toxicity of new drugs will hasten the process of introducing new and improved drugs into the market, as biofabricated tissue constructs will not only allow for testing of these drugs on native-like tissues but will also provide an opportunity to study physiological responses to their effects (40).…”
Section: Corneamentioning
confidence: 99%